Notes on the taxonomy of some “Astaena” species described by Burmeister (Coleoptera: Scarabaeidae: Melolonthinae) - Pacheco, Thaynara L.; Monné, Marcela L.; Vaz-De-Mello, Fernando Z.; Ahrens, Dirk (Zootaxa, 2020)
In the framework of the taxonomic revision of South American Sericini (Coleoptera: Scarabaeidae: Melolonthinae), we examined the type specimens of the species described by Burmeister (1855) in the genus Astaena Erichson, 1847. A few taxa resulted to not belong to the South American Sericini fauna, either due to different geographical provenience or due to incorrect systematical placement within Sericini. Two new combinations and one new synonymy are proposed: Neoserica pubescens (Burmeister, 1855), new combination (= Neoserica subsetosa Ahrens & Fabrizi, 2016: 121, new synonymy) and Manonychus robustus (Burmeister, 1855), new combination.